FRI0556 A Multi-Biomarker Disease Activity Blood Test in Patients with Juvenile Idiopathic Arthritis. (10th June 2014) - Ringold, S.; Lu, L.; Wallace, C.; Sasso, E.; Eastman, P.S.
Abstract : Background: Current measures of disease activity for juvenile idiopathic arthritis (JIA), including physician global assessment of disease activity and active joint count, are subjective and potentially confounded by disease heterogeneity and comorbid conditions. A multi-biomarker disease activity assay (MBDA) incorporating a panel of biomarkers may provide objective and quantitative data regarding disease activity that would be of great value to physicians caring for children with JIA. An MBDA blood test that measures serum concentrations of 12 inflammatory biomarkers to produce a disease activity score (Vectra® DA) has been validated for rheumatoid arthritis (RA) in adults. Objectives: To evaluate the MBDA blood test in children with polyarticular or extended oligoarticular JIA. Methods: Samples were analyzed from a cohort of children with established JIA treated at Seattle Children's Hospital & Research Institute (SCHRI), including 57 samples from 49 children with polyarticular (n=35) or extended oligoarticular JIA (n=22), and samples from 30 children with polyarticular JIA participating in the Trial of Early Aggressive Therapy in JIA (TREAT) prior to initiation of therapy. Samples were classified as clinically inactive disease or active disease using the ACR provisional criteria for clinically inactive disease (CID). The Juvenile Arthritis Disease Activity Score (JADAS) was calculated based on 10 joints and samples were analyzed for 18 individual biomarkers, 12 of which comprise the MBDA test for RA and an MBDA score calculated. Results: The mean and median JADAS values for the cohort (n=87) were 12.3 and 7.5, respectively (range 0-31.6). The mean and median MBDA scores were 21 and 14 for the children with CID, and 41 and 42 for children with active disease. The correlation between the MBDA score and JADAS was r=0.77 (see figure). Several individual biomarkers, including IL-6, MMP-3, TNF-R1 and YKL-40, exhibited higher concentrations in the active disease group compared with the CID group. Conclusions: These data demonstrate that the MBDA score detects differences in biomarker concentrations among patients with JIA and correlates with the level of clinical disease activity. Disclosure of Interest: S. Ringold: None declared, L. Lu Shareholder of: Crescendo Bioscienc, Employee of: Crescendo Bioscience, C. Wallace: None declared, E. Sasso Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, P. Eastman Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience DOI: 10.1136/annrheumdis-2014-eular.5846